The Implementation of Balanced Scorecard as an Alternative Performance Measurenment at Samsat Mataram - Komaryati, Nungki; M., Akram; Prayitno, Basuki (International Journal of Scientific Research and Management (IJSRM), 2018)
This study aims to examine the possibility of applying balanced scorecard to SAMSAT Mataram Office. The assertion of the importance of a more comprehensive measurement method that traditional measurements we know so far is very difficult to measure the intangible assets. Therefore, a performance measurement system that is able to measure the value of the intangible assets is required to estimate and deliver an economic success of the organization. Implementation of a balanced scorecard supported by the correct reporting system will support the realization of good governance. This research uses qualitative approach with Case Study research strategy.The result of the research shows that to increase the strategic role as public service provider institution with excellent service system and mechanism requires uniformity between performance measurement result with actual condition of office / institution performance or government organization. As a method of measuring the performance of the balanced scorecard framework is perceived to be relatively comprehensive, coherent, balanced and measurable compared to the measurement of AKIP performance in SAKIP, therefore the balance scorecard framework is then perceived as necessary for government agencies such as SAMSAT to be implemented in office performance measurement. Office performance measurement using the balance scorecard is not intended to replace the existing LAKIP framework within SAKIP, but rather an attempt to provide input within the AKIP framework by including key performance indicators that have not been considered in the SAKIP framework.